Ação do fator estimulador de colônias de granulócitos em úlceras traumáticas confeccionadas na língua de ratos submetidos à radioterapia : avaliação clínica e histológica - Jasper, Juliana (2016)
Radiation-induced oral mucositis (OM) is a highly debilitating side effect, which affects almost all patients with head and neck malignancies undergoing radiotherapy (RT). The severity of this injury is directly related to factors associated with the therapy itself and the individual characteristics of each patient. To date, there is no standard treatment protocol for this condition. Therefore, the present study aimed to evaluate clinically and histologically the effect of granulocyte colony-stimulating factor (G-CSF) on the healing of traumatic ulcers produced in the tongue of Wistar rats undergoing RT. The animals were randomly divided into 4 groups: 1) RT + traumatic ulcer + Filgrastim; 2) RT + traumatic ulcer + saline; 3) no RT + traumatic ulcer + Filgrastim; 4) no RT + traumatic ulcer. Filgrastim (r-metHuG-CSF), a recombinant G-CSF, was injected subcutaneously into the animals once daily, beginning 1 day after a single-dose radiation protocol (30 Gy), immediately after the traumatic ulcer was made. At the end of a 7-day experimental period, animals were euthanized and had their tongue surgically removed, processed, and stained with hematoxylin and eosin (HE). Clinically, all groups differed significantly in presence and size of traumatic ulcers, and the irradiated groups also differed significantly in severity of radiation-induced OM. Filgrastim-treated groups, submitted or not to RT, showed a better performance in this aspect. Histologically, there was an increased inflammatory response in the nonirradiated groups, with no statistically significant difference between the study drug and the respective control groups. Based on the present clinical results, we conclude that the use of Filgrastim reduced the manifestation and severity of trauma-induced ulcers and radiation-induced OM. This condition has a complex pathogenesis, which requires further detailed investigations on the actual role of G-CSF in its management before a formal recommendation regarding its use for this purpose can be made.